Strengthening personal growth: The effects of a strengths intervention on personal growth initiative. Issue 1 (21st September 2018) - van Woerkom, Marianne; Meyers, Maria Christina
Abstract : Personal growth is not only a central individual need but also a key requirement for organizational success. Nevertheless, workplace interventions aimed at stimulating the personal growth of employees are still scarce. In this study, we investigated the effectiveness of an intervention that aimed at the identification, development, and use of employee strengths in stimulating personal growth initiative. We conducted a field experiment with a sample of 84 educational professionals who were either assigned to a strengths intervention or a wait‐list control group. In a 1‐month follow‐up study, we found that the intervention had a direct effect on general self‐efficacy (GSE) and an indirect effect on personal growth initiative. Moreover, in line with plasticity theory we found that the intervention was especially effective for participants with low to medium initial levels of GSE. We conclude that a strengths intervention may provide a brief and effective tool for organizations that aim for self‐directed learning among their staff, in particular when offered to employees who lack confidence in their own abilities. Practitioner points: In a 1 month follow‐up study, we found that a strengths intervention had a positive direct effect on general self‐efficacy and an indirect effect on personal growth initiative. In line with plasticity theory, we found that the strengths intervention was especially effective for participants with low to medium initial levels of general self‐efficacy.